2014
DOI: 10.1002/jsfa.6870
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ZnCl2 on green Spanish‐style table olive packaging, a presentation style dependent behaviour

Abstract: Zinc chloride was less efficient than potassium sorbate as a yeast inhibitor in green Spanish-style olives, showing clear presentation style dependent behaviour for this property. Its presence produced significant changes in chemical parameters but scarcely affected colour or sensory characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Besides, when the sensory data were subjected to PLS analysis, the projections of attribute loadings and treatments scores on the first two PCs positively related the control to bitter and the kinesthetic sensations while the product with 0.075% ZnCl 2 was associated with high titratable acidity and acid scores ( 11 ). In a first approach for the preparation of green Spanish-style olive packaging containing ZnCl 2 , however, no effect of Zn content was observed, possibly due to the lye treatments used for debittering ( 12 ). Further comparisons between packaged green olives using ZnCl 2 and potassium sorbate or sodium benzoate showed that the panelists preferred the olives packaged with Zn against those containing the classical preservatives but no relationship with bitter was found (private communication).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, when the sensory data were subjected to PLS analysis, the projections of attribute loadings and treatments scores on the first two PCs positively related the control to bitter and the kinesthetic sensations while the product with 0.075% ZnCl 2 was associated with high titratable acidity and acid scores ( 11 ). In a first approach for the preparation of green Spanish-style olive packaging containing ZnCl 2 , however, no effect of Zn content was observed, possibly due to the lye treatments used for debittering ( 12 ). Further comparisons between packaged green olives using ZnCl 2 and potassium sorbate or sodium benzoate showed that the panelists preferred the olives packaged with Zn against those containing the classical preservatives but no relationship with bitter was found (private communication).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the Aloreña de Málaga prepared with 0.075% ZnCl 2 in the cover brine represented a novel Zn fortified table olive presentation ( 11 ). On the contrary, ZnCl 2 added to green Spanish-style table olive packaging showed a lower inhibitory effect than potassium sorbate against yeasts ( 12 ). The loss of inhibitory efficiency could not be attributed to hydroxytyrosol or NaCl since, in their presence, the fungicidal activity of ZnCl 2 and ZnSO 4 against table olive yeasts, using synthetic medium, remained inalterable ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the acidification step is useful in helping the fermentation process and it has no effect on the sensory profile of olives. Bautista-Gallego et al [117] used fermented Manzanilla olives to evaluate the influence of the addition of zinc chloride (ZnCl 2 at 0.00%, 0.25%, 0.50%, 0.75% and 1.00%) to brine on increasing the olives' shelf life and improving their sensory properties. A panel of twelve trained members used two protocols [81].…”
Section: Treated Green Olives or "Spanish Style"mentioning
confidence: 99%
“…To date, several studies have investigated the partial or complete substitution for NaCl in fermented green and black olives, and olive juice [58,76,[80][81][82][83][84]. Products were obtained that had a balanced mineral composition and enhanced nutritional value based on a controlled process that prevented deterioration and spoilage and improved the sensorial characteristics of the products [58,[82][83][84][85][86][87][88].…”
Section: Reducing Salt In the Processing Of Table Olivesmentioning
confidence: 99%
“…The reduction in Na can be made possible by using substitutes for NaCl, such as potassium chloride (KCl), magnesium chloride (MgCl 2 ), calcium chloride (CaCl 2 ), zinc chloride (ZnCl 2 ), zinc sulfate, and/or zinc perchlorate. Each of these compounds has an antimicrobial effect on pathogens, yeasts, and toxigenic fungi, and each of them also is permitted for the preparation of fortified foods within the current EU legislation (Commission Regulation EU 432/2012) [76,[80][81][82][87][88][89][90].…”
Section: Reducing Salt In the Processing Of Table Olivesmentioning
confidence: 99%